Improving health and efficiency with strategic social media use in health organizations: A critical review of the status Quo - Aydın, Gökhan (IGI Global, 2021)
The emergence of social networking systems as mainstream applications and an inherent element of daily life is a phenomenon observed throughout the world as the worldwide social media users exceeds 2.7 billion. Similar to other sectors, healthcare organizations have also started benefiting from social media in distinct ways such as collecting feedback, educating, communicating and supporting patients and citizens. Social networks can act as remarkable channels for healthcare providers, governmental institutions, pharmaceutical companies, hospitals and others to educate, communicate to, listen, connect to and engage existing and potential customers, patients, physicians and healthcare professionals. Despite the various benefits offered, health institutions, health professionals and stakeholders are reluctant to utilize social media due to several barriers and lack of expertise. This chapter aims to provide a better understanding on the ways healthcare companies can utilize social networks in detail to overcome use barriers and obtain related benefits.
Keywords: Improving Health; Social Media; Status Quo